Numerical study of integrated latent heat thermal energy storage devices using nanoparticle-enhanced phase change materials. (December 2019) - Akhmetov, B.; Navarro, M.E.; Seitov, A.; Kaltayev, A.; Bakenov, Z.; Ding, Y.
Graphical abstract: Highlights: Three-dimensional CFD simulation fosters improved storage design. Efficiency is properly studied using characterization results in simulation. Thermal energy is effectively stored using two different phase change materials. Nano-Al2 O3 addition into the materials improves charging and discharging efficiency. Such storage with enhanced operating efficiency fits into smart heating networks. Abstract: Two sequentially integrated LHTES devices based on paraffin waxes (PW), PW-L and PW-H with different phase change temperature ranges are numerically studied using Comsol Multiphysics for efficient thermal energy storage (TES). Thermal properties of the PWs are characterized and aluminum oxide nanoparticles (nano-Al2 O3 ) are dispersed into the PWs to improve their heat transfer ability. According to the laser flash apparatus results, when the nano-Al2 O3 composes 4 wt% of the mass of the PW-L, its thermal diffusivity can be enhanced up to 40%. The same amount of the nano-Al2 O3 improves the thermal diffusivity of the PW-H approximately by 25%. Further characterization studies show that the incorporation of the nano-Al2 O3 does not significantly change the specific heat capacity, latent heat of melting and cooling of the PCMs, but improves the heat transfer efficiency of the PCMs. Measured thermal properties of the PCMs are considered as input data in the numerical simulation of operating regimes of the devices. The full charging time of the integrated LHTES devices is reduced by 57 min and 106 min when the nano-Al2 O3 composed 2 wt% and 4 wt% of the mass of the PCMs respectively. Likewise, the full discharging time of the integrated devices is decreased by 32 min and 74 min by the addition of the nano-Al2 O3 . Such reductions lead to improved charging and discharging efficiency of the LHTES devices. Moreover, simulation results show that the total amount of the stored energy in the devices fairly approximates the differential scanning calorimetry (DSC) results.